Computational blast response of tin slag polymer concrete bunker sandwiched by carbon fibre reinforced polymer skins - Mahmudul, Hasan (unimas, 2025)
Motivated by the increasing threats of terrorist activities and the urgent requirement to protect civilian buildings from explosive events, this study aims to evaluate the blast-resistant characteristics of sandwich polymer concrete bunkers (SPCB) with tin slag as material inclusion which is externally strengthened by carbon fibre-reinforced polymer skins. The performance of the SPCB was compared with that of the sandwiched conventional reinforced plain concrete bunkers (SCB). The research utilized ABAQUS/CAE 6.14 software with the CONWEP function to analyse the effects of 1kg, 5kg, 10kg, and 25kg TNT charges from various blast points that are referred to as stand-off distances of 0.1, 0.25, 0.5, 1, 2 and 2.5 meters from SPCB with core thicknesses of 200 mm, 250mm, 300mm, and 500 mm. The results found that enhanced TNT charge and shorter distances caused an increase in deflection, von Mises stress, principal stress, and damage. Notably, a 200 mm thick SPCB exhibited a perforation size of only 0.28 m², compared to 1.14 m² in SCB representing 75.44% reduction in damage. A 250 mm and 500 mm SPCB did not fail under heavy blast load. The trend indicates that as the core thickness increases, the blast resistance improves. In contrast, a 500 mm thick SCB sustained 34.8% perforation damage under a 25 kg TNT blast at a 1-meter distance, while the SPCB showed no damage. Hence, it is proven that polymer concrete with CFRP shell as bunker is high blast-resistant. Mathematical models have been proposed to predict maximum von Mises and principal stress based on TNT charge, stand-off distance, and concrete core thickness. The study confirms that the SPCB design provides superior blast resistance compared to SCBs, making it suitable for high-risk blast-resistant facilities.